Frequency and indications of Caesarean Section at Department of Obstetrics and Gynaecology Unit-III, Civil Hospital Quetta (Medical Forum Monthly, 2024)
Objective: To determine the frequency and indications of caesarean section at Department of Obstetrics and Gynaecology Civil Hospital Quetta, Unit-III.Study Design: A descriptive study.Place and Duration of Study: Department of Obstetrics and Gynaecology unit-III, Civil hospital Quetta, from May 2011 to April 2012.Materials and Methods: This study was performed on all the patients admitted during study period for both emergency and planned caesarean section, excluding cases of ruptured uterus on laprotomy. Data was collected from labor room and operation theater records. Information was obtained on frequency, indications of caesarean section and patient related demographic variables. Descriptive statistics were calculated on SPSS version.Results: Out of 4690 deliveries, caesarean section was performed on 626 patients. The rate of caesarean section was 12.62%. Emergency caesarean sections were 570(91%) while 56(8.9%) were planned caesarean sections. The commonest indication was repeat caesarean section 337(53.8%) followed by obstructed labor in 150(23.9%) cases. Other indications were antepartum haemorrhage 52(8.3%), breech presentation 39(6.2%), miscellaneous 48 (7.6%) for bad obstetrical history, fetal distress, pregnancy induced hypertension, eclampsia, other malpresentations.Conclusion: Caesarean section is a common form of delivery. Repeat cesarean section and obstructed labor are the most frequent indications